2014
DOI: 10.1002/prot.24511
|View full text |Cite
|
Sign up to set email alerts
|

Decoding the structural events in substrate‐gating mechanism of eukaryotic prolyl oligopeptidase using normal mode analysis and molecular dynamics simulations

Abstract: Prolyl oligopeptidase (POP) is a serine protease, unique for its ability to cleave various small oligopeptides shorter than 30 amino acids. POP is an important drug target since it is implicated in various neurological disorders. Although there is structural evidence that bacterial POPs undergo huge interdomain movements and acquire an "open" state in the substrate-unbound form, hitherto, no crystal structure is available in the substrate-unbound domain-open form of eukaryotic POPs. Indeed, there is no differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 55 publications
0
22
0
Order By: Relevance
“…Both induced fit and conformational selection are consistent with substrate hydrolysis kinetic studies of PREP, showing that the experimental kinetic parameters are substrate-dependent and that a physical rather than a chemical step is rate determining 13 . Since functionally essential residues in the substrate binding pocket and the inter-domain interface are conserved between species, domain movement may be common in the catalytic cycle of all PREPs 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Both induced fit and conformational selection are consistent with substrate hydrolysis kinetic studies of PREP, showing that the experimental kinetic parameters are substrate-dependent and that a physical rather than a chemical step is rate determining 13 . Since functionally essential residues in the substrate binding pocket and the inter-domain interface are conserved between species, domain movement may be common in the catalytic cycle of all PREPs 14 .…”
Section: Introductionmentioning
confidence: 99%
“…As in our initial report of artificial enzyme formation using SPAAC, [11] an amber codon was introduced into the POP gene [15] to replace the catalytically active serine (S477) with a Z residue (Z477). Four alanine mutations (E104A, F146A, K199A, D202A) were introduced to open a small pore in the POP structure [16] to allow cofactor entry into the active site. A codon optimized POP gene was used as a template for genetic manipulation, and the resulting scaffold, POP-ZA 4 , was expressed in high yield in E. coli with essentially quantitative Z incorporation.…”
mentioning
confidence: 99%
“…Various efforts such as sequence search method and true homologue collection method have been made with a single query sequence to choose the ''true'' hits. These sequence search methods enabled the identification of possible true homologues which cannot be picked by direct BLAST search [6].…”
Section: Single Representative For Sequence Searchesmentioning
confidence: 99%
“…The active site is hidden in a large cavity formed by the interface of propeller and hydrolase domain [5]. The molecular dynamics simulation studies have suggested that opening of two domains is the only possible pathway for the substrate entry in POPs [6]. In order to understand the role of POP in biological and disease processes, both synthetic and natural ligands have been tested [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation